LIQUIDITY RISK MANAGEMENT IN SHARIA BANKS - Nurfitriah Nurfitriah (JASIE, 2024)
Liquidity management refers to the efforts of companies or financial institutions to manage and control the availability and use of sufficient funds to meet their immediate or sudden financial obligations. This aims to maintain smooth operations, fulfill payment obligations, and avoid the risk of a lack of liquidity. Liquidity management involves careful planning, monitoring and control of financial assets and liabilities. Liquidity management in Islamic banks has principles that are in accordance with Islamic principles in banking activities. Liquidity instruments at Islamic banks can be obtained from collecting third party funds (DPK), borrowing on the Islamic money market, purchasing Islamic SBIs, seeking domestic or foreign investors, or from other funding sources.Keywords: Liquidity, Risk, Islamic Banks